HUBUNGAN PENGETAHUAN DENGAN MOTIVASI PADA PASIEN HEMODIALISA - Tiarnida Nababan (Universitas Prima Indonesia, 2021)
Hemodialysis is a method of dialysis therapy that is used to removes fluids and waste products from the body when acutely or progressively the kidneys are unable to carry out the process. The purpose of this study was to explain the relationship between knowledge and motivation in patients undergoing hemodialysis at the RSU. Royal Prima Medan. This research is a correlation with a cross-sectional approach. The population is 63 people, the sampling technique is the total sampling technique, so the sample is 63 respondents. The data of analysis using chi-square test. Based on the results obtained significant value (2-sided) of 0.026, Ha is accepted, meaning there is a relationship between knowledge and motivation in hemodialysis patients. The results of the study on respondents' knowledge obtained that the majority had good knowledge as many as 8 people (12.7%), 26 people (41.3%), and 29 people (46%). This study concludes that there is a significant relationship between knowledge and motivation in hemodialysis patients.